(untitled) (Journal of the College of Education for Women, 2019)
Cryptographic applications demand much more of a pseudo-random-sequencegenerator than do most other applications. Cryptographic randomness does not mean juststatistical randomness, although that is part of it. For a sequence to be cryptographicallysecure pseudo-random, it must be unpredictable.The random sequences should satisfy the basic randomness postulates; one of them isthe run postulate (sequences of the same bit). These sequences should have about the samenumber of ones and zeros, about half the runs should be of length one, one quarter of lengthtwo, one eighth of length three, and so on.The distribution of run lengths for zeros and onesshould be the same. These properties can be measured deterministicallyand then compared tostatistical expectations using a chi-square test.In this paper the Run Criterion, is calculated, it can be calculated for any key generatorbefore it be implemented or constructed (software or hardware).The cryptosystems: Linear,Product and Brüer are chosen as study cases.